PENGARUH KEADILAN ORGANISASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) PAMONG TAMAN DEWASA (SMP) DI PERGURUAN TAMAN SISWA YOGYAKARTA TAHUN 2016 - Hasbi Apriandaka; Prayekti Prayekti (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study was to analyze the influence organizational justice on OCB, influence job satisfaction on OCB, organizational commitment on OCB, and influence organizational justice, job satisfaction, and organizational commitment on OCB teacher at Taman Dewasa (Junior High School), Perguruan Tamansiswa of Yogyakarta City.The population of this study is all teacher at Taman Dewasa (Junior High School) Perguruan Tamansiswa of Yogyakarta City. The variabels are organizational justice (X1), job satisfaction (X2), organizational commitment (X3) and OCB (Y).Â The sampelsÂ is about 61 teacher. Data collection using a questionnaire, while data analysis techniques using multiple regression analysis by the F-test and T-test, and the classical assumption test of multicollinearity test, normality test, and heteroscedasticity.The results with level of significance 5% or 0,05 showed that organizational justice haven significant effect on OCB (0,035< 0,05), job satisfaction have significant effect on OCB(0.001< 0,05), organizational commitment have significant effect on OCB (0.023< 0,05), and organizational justice, training, and motivation has significant effect on OCB teacher at Taman Dewasa (Junior High School) Perguruan Tamansiswa ofÂ Yogyakarta City